Гнучкі композиційні сцинтилятори на основі мікро- та нанопорошків ZnWO4 - Tinkova, V.; Yakubovskaya, A.; Tupitsyna, I.; Abashin, S.; Puzan, A.; Tretyak, S. (PE "Politekhperiodika", Book and Journal Publishers, 2019)
Nano-sized and micro-sized ZnWO4 powders were obtained by different methods: hydrothermal synthesis with microwave heating, molten salt method, solid-state synthesis and сrushing of bulk crystals. Their morphological features were studied using transmission electron microscope and scanning electron microscope. The obtained nano- and micro-sized powders were used as fillers for flexible composite scintillators. The silicon rubber was used as a binder. The luminescent characteristics and scintillation performance of composite scintillators were measured. The dependence of scintillation performance of flexible scintillators on the morphological features of ZnWO4 nanocrystallites was demonstrated. The flexible composite scintillator based on zinc tungstate obtained by solid-state synthesis with lithium nitrate addition was obtained and investigated. Its scintillation performance was close to that of a ZnWO4 single crystal.